Policy implementation strategies to address rural disparities in access to care for stroke patients - Rasool, Aysha; Bailey, Moriah; Lue, Brittany; Omeaku, Nina; Popoola, Adebola; Shantharam, Sharada S.; Brown, Amanda A.; Fulmer, Erika B. (Frontiers in Health Services, 2023)
Context Stroke systems of care (SSOC) promote access to stroke prevention, treatment, and rehabilitation and ensure patients receive evidence-based treatment. Stroke patients living in rural areas have disproportionately less access to emergency medical services (EMS). In the United States, rural counties have a 30% higher stroke mortality rate compared to urban counties. Many states have SSOC laws supported by evidence; however, there are knowledge gaps in how states implement these state laws to strengthen SSOC. Objective This study identifies strategies and potential challenges to implementing state policy interventions that require or encourage evidence-supported pre-hospital interventions for stroke pre-notification, triage and transport, and inter-facility transfer of patients to the most appropriate stroke facility. Design Researchers interviewed representatives engaged in implementing SSOC across six states. Informants (n = 34) included state public health agency staff and other public health and clinical practitioners. Outcomes This study examined implementation of pre-hospital SSOCs policies in terms of (1) development roles, processes, facilitators, and barriers; (2) implementation partners, challenges, and solutions; (3) EMS system structure, protocols, communication, and supervision; and (4) program improvement, outcomes, and sustainability. Results Challenges included unequal resource allocation and EMS and hospital services coverage, particularly in rural settings, lack of stroke registry usage, insufficient technologies, inconsistent use of standardized tools and protocols, collaboration gaps across SSOC, and lack of EMS stroke training. Strategies included addressing scarce resources, services, and facilities; disseminating, training on, and implementing standardized statewide SSOC protocols and tools; and utilizing SSOC quality and performance improvement systems and approaches. Conclusions This paper identifies several strategies that can be incorporated to enhance the implementation of evidence-based stroke policies to improve access to timely stroke care for all patient populations, particularly those experiencing disparities in rural communities.